Dimensional Assessment and Error Analysis of 3D CAD Models Manufactured with Bound Metal Deposition - Yasya Khalif Perdana Saleh; Rifky Ismail; Jamari Jamari; I Nyoman Jujur; Poki Agung Budiantoro; Sri Ramayanti; Rochmad Winarso (International Journal of Engineering and Technology Innovation, 2026)
This study evaluates dimensional deviations of 316L stainless steel components produced using the Bound Metal Deposition (BMD) method. The evaluation covers four production stages: CAD modeling, slicing, printing, and sintering. The approach involves experimental measurements and finite element simulations to assess accuracy. Results indicate an average dimensional deviation of 6%, with height-related features showing the most significant errors due to anisotropic shrinkage and inconsistencies in layer deposition. The widely used 1.16 scale factor is inadequate for precise dimensional recovery. Instead, a revised scale factor of 1.13 is developed through empirical analysis and validated using ANSYS simulation. This new factor shows better agreement with the original CAD design. Furthermore, the achieved dimensional accuracy falls within clinically accepted tolerances for dental implants (0.19-0.36 mm), making it suitable for biomedical applications. Overall, these findings provide a validated framework for dimensional calibration in BMD, improving the accuracy of patient-specific medical devices.